Utilizing The Tiktok Application As An Online Business Learning Media - Juwairia, Juwairia; Tumanggor, Ginagor; Mustaqim, Bima (Universitas Negeri Malang, 2023)
TikTok, a very popular platform today, made a comeback in early 2020 and even surpassed Instagram as the most popular app in the App Store. The purpose of this research is to utilize the tiktok application as a learning medium. The research was conducted for one week during Online Business learning hours with material on designing an online business. The research consisted of two cycles, where each cycle consisted of two meetings which included planning, action, observation, and reflection. The data collection tools used included student observation sheets, teacher observation sheets, questionnaires, tests, and TikTok promotional video assignments. The subjects of this study were all students of class XI BDP at SMKN 1 Pemulutan. The results showed that students' promotion skills increased from cycle I to cycle II. Some students have mastered or are already good at promoting online business subjects. This can be seen from good test scores, increased task completion both in terms of time and quality. So that it can be said that the use or utilization of the TikTok application can improve student promotion skills.Abstrak TikTok, sebuah platform yang sangat terkenal saat ini, bahkan melampaui Instagram sebagai aplikasi paling populer di App Store. Tujuan dari penelitian ini adalah untuk memanfaatkan aplikasi tiktok sebagai media pembelajaran. Penelitian dilakukan selama satu minggu pada jam pembelajaran Bisnis Online dengan materi merancang bisnis online. Penelitian terdiri dari dua siklus, dimana setiap siklus terdiri dari dua kali pertemuan yang mencakup perencanaan, tindakan, observasi, dan refleksi. Alat pengumpulan data yang digunakan meliputi lembaran observasi peserta didik, lembaran observasi guru, angket, tes, dan tugas video promosi TikTok. Subjek penelitian ini adalah seluruh peserta didik kelas XI BDP di SMKN 1 Pemulutan. Hasil penelitian menunjukkan keterampilan promosi peserta didik mengalami peningkatan dari siklus I ke siklus II. Sebagian siswa sudah dapat menguasai atau sudah baik dalam melakukan promosi dalam mata Pelajaran bisnis online. Hal ini terlihat dari nilai tes yang baik, peningkatan penyelesaian tugas yang baik dari segi waktu maupun kualitas. Sehingga dapat dikatakan penggunaan atau pemanfaatan aplikasi TikTok dapat meningkatkan keterampilan promosi siswa.